2021
DOI: 10.1038/s41598-020-80124-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of tomosynthesis-guided vacuum assisted breast biopsy of ultrasound occult lesions

Abstract: This study aims to evaluate the diagnostic accuracy of digital breast tomosynthesis-guided vacuum assisted breast biopsy (DBT-VABB) of screening detected suspicious mammographic abnormalities comprising of calcifications, asymmetric densities, architectural distortions and spiculated masses. In this institutionally approved study, a total of 170 (n = 170) DBT-VABB were performed, 153 (90%) were for calcifications, 8 (4.7%) for spiculated mass, 5 (2.9%) for asymmetric density and 4 (2.4%) for architectural dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Along with DCIS, high-risk lesions as mentioned above are listed as contributors to underestimation rates. 20 , 23 , 26 , 30 , 31 Our DCIS underestimation rate of 10.3% ( n = 3) is comparable to results from other studies ( Table 5 ). All three of our cases involved the upgrading of DCIS to invasive carcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Along with DCIS, high-risk lesions as mentioned above are listed as contributors to underestimation rates. 20 , 23 , 26 , 30 , 31 Our DCIS underestimation rate of 10.3% ( n = 3) is comparable to results from other studies ( Table 5 ). All three of our cases involved the upgrading of DCIS to invasive carcinoma.…”
Section: Discussionsupporting
confidence: 89%
“…In comparison to Mendez et al, with 25.0%, and Bohan et al, with 12.5%, our malignancy rate amongst mass-like lesions is high. 21,26 However, there were no circumscribed masses in our study (they were all described as having a spiculated or indistinct margin). When excluding the circumscribed masses from the study by Mendez et al, the malignancy rate amongst mass-like lesions is 66.0%.…”
Section: Discussionmentioning
confidence: 67%
“…No statistically significant association between complications and needle gauge or guiding modality was observed in this study, similar to findings published by Burbank et al Alike Bohan et al's experience (55%), most patients in this study reported mild pain (62%). 35 Mean pain score was 3 which was close to findings of Seely et al (3.1), pointing to the good overall tolerance of VABB. 36 Retrospective design of this study, small sample size, and limited follow-up are limitations of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Kettritz et al [45] obtained sensitivities and NPVs above 99%. Bohan et al [46] found a specificity of 100% and sensitivity of 91.3% with a PPV of 100% for malignancy and a high NPV (81.8%) for benignity but a higher false-negative rate of 20% due to smaller sample size.…”
Section: Discussionmentioning
confidence: 99%